Determination of antimicrobial activity of some commercial fruit (apple, papaya, lemon and strawberry) extracts against bacteria causing urinary tract infection - Liya, Sabiha Jahan (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.